Moliyaviy siyosat va xo„jalik subyektlari faoliyatini tartibga solishning soliqsiz usullari - Xamrayev Oybek (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Non-tax methods of regulating financial policy and the activities of economic entities play a crucial role in ensuring the economic stability of a state. This thesis analyzes mechanisms such as subsidization, credit-tax policies, currency restrictions, and export-import controls, which are applied alongside the tax system. The aim is to enhance the efficiency of economic entities' operations, attract investments, and stimulate economic growth through the effective use of non-tax tools.